PEMBERIAN PROBIOTIK UNTUK OPTIMALISASI KELANGSUNGAN HIDUP DAN PERTUMBUHAN IKAN GABUS LOKAL (Channa sp.) HASIL DOMESTIKASI - Fazril Saputra; Yusran Ibrahim; Dini Islama; Mahendra Mahendra; Muhammad Arif Nasution; Ihsanul Khairi (JURNAL PERIKANAN TROPIS, 2022)
AbstractSnakehead fish (Channa sp.) is one of Indonesia's native freshwater commodities that has been successfully domesticated by fish farmers, yet the domesticated snakehead fish culture still has problems, namely the low survival and growth of local snakehead fish. Overcoming this problem requires a technology that can optimize the survival and growth of the domesticated snakehead fish (Channa sp.). One technology that can be applied is the use of probiotics. This reserach aimed to examine different probiotics through feed to optimize the survival and growth of domesticated snakehead fish (Channa sp.). This research was conducted with an experimental method. The experimental design used was a completely randomized design with 4 treatments and 3 replications. The treatments were control treatment (P0), treatment with probiotic composition of Lactobacillus sp., Bacillus spp. and Nitrosomonas sp. (P1), treatment with probiotic composition of Lactobacillus casei and Saccharomyces cerevisiae (P2), and treatment with probiotic composition of Lactobacillus sp., Acetobacter, Rhodobacter sp., yeast (P3). The results showed that different probiotic feeding had a significant effect (P<0.05) on the survival parameters and different probiotic feeding compositions had no significant effect (P>0.05) on the growth parameters. The composition of Lactobacillus casei and Saccharomyces cerevisiae probiotics is the best probiotic composition to increase survival and growth of domesticated snakehead fish.Keywords: Domestication, Growth, Survival Rate, Probiotic